Cost-effectiveness analysis of apixaban compared to low-molecularweight heparins and vitamin k antagonists for treatment and secondary prevention of venous thromboembolism - Isabel Elías; Itziar Oyagüez; Luis Antonio Alvarez-Sala; Fernando García-Bragadoa; Andrés Navarro; Paloma González; Fernando de Andrés-Nogales; Javier Soto (Elsevier, 2016)
Objective: Cost-effectiveness analysis of a 6-month treatment of apixaban (10 mg/12h, first 7 days; 5 mg/12h afterwards) for the treatment of the first event of venous thromboembolism (VTE) and prevention of recurrences, versus low-molecular-weight heparins/vitamin K antagonists treatment (LMWH/VKA). Material and methods: A lifetime Markov model with 13 health states was used for describing the course of the disease. Efficacy and safety data were obtained from AMPLIFY and AMPLIFY-EXT clinical trials; health outcomes were measured as life years gained (LYG) and quality-adjusted life years (QALY). The chosen perspective of this analysis has been the Spanish National Health System (NHS). Drugs, management of VTE and complications costs were obtained from several Spanish data sources (€, 2014). A 3% discount rate was applied to health outcomes and costs. Univariate and probabilistic sensitivity analyses (SA) were performed in order to assess the robustness of the results. Results: Apixaban was the most effective therapy with 7.182 LYG and 5.865 QALY, versus 7.160 LYG and 5.838 QALYs with LMWH/VKA. Furthermore, apixaban had a lower total cost (€13,374.70 vs €13,738.30). Probabilistic SA confirmed dominance of apixaban (led to better health outcomes with less associated costs) in 89% of the simulations. Conclusions: Apixaban 5 mg/12h versus LMWH/VKA was an efficient therapeutic strategy for the treatment and prevention of recurrences of VTE from the NHS perspective.